Challenges in Teaching Real Analysis classes at University of PGRI, South Sumatra, Indonesia - Septiati, Ety; Karjanto, Natanael (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis paper discusses our experience and challenges in teaching advanced undergraduate Real Analysis classes for Mathematics Education students at University of PGRI (Persatuan Guru Republik Indonesia) Palembang, South Sumatra, Indonesia. We observe that the syllabus contains topics with a high level of difficulty for the students who are specialized in education and intend to teach mathematics at the secondary level. The conventional lecturing method is mainly implemented during the class, with some possible variationsof the method, including the Texas method (also known as Mooreâs method) and the small group guided discovery method. In particular, the latter method has been implemented successfully for a Real Analysis class at Darmouth College, New Hampshire by DumitrasÂ¸cu in 2006. Although it is a real challenge to apply a specific teaching method that will be able to accommodate a large number of students, the existing teaching activities can still be improved and a more effective method could be implemented in the future. Furthermore, the curriculum contents should be adapted for an audience in mathematics education to equip them for their future career as mathematics teachers. Any constructive suggestions are welcome for the improvement of our mathematicseducation system at the university as well as in the national scale.